Executive Functions Among Fifth-grade Pupils With Reading Difficulties From The Perspectives Of Teachers And Parents - Ghedhaifi, Hind (جامعة الوادي - University of Eloued, 2024)
This study aims to investigate individual differences in executive functions among fifth-grade elementary pupils with reading difficulties, according to the variable of gender, as perceived by teachers and parents. The research questions were formulated as follows: Are there statistically significant differences in the executive functions of finalstage elementary pupils with reading difficulties, as reported by teachers, based on the gender variable (males vs. females)? Are there statistically significant differences in the executive functions of final-stage elementary pupils with reading difficulties, as reported by parents, based on the gender variable (males vs. females)? The comparative descriptive methodology was adopted due to the nature of our subject, and data collection relied on the Executive Functions Scale. The study included a sample of 80 participants, consisting of 40 males and 40 females, selected purposefully. The findings revealed that there were no statistically significant differences in the executive functions of final-stage elementary pupils with reading difficulties, as perceived by teachers, based on the gender variable (males vs. females). However, there were statistically significant differences in the executive functions of final-stage elementary pupils with reading difficulties, as perceived by parents, based on the gender variable (males vs. females).
A Field Study In Some Elementary Schools In El-oued
مقال
Keywords: Reading difficulties, executive functions, pupils, parents, teachers